2019
DOI: 10.1101/642751
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aversive Learning Increases Release Probability of Olfactory Sensory Neurons

Abstract: Predicting danger from previously associated sensory stimuli is essential for survival.Contributions from altered peripheral sensory inputs are implicated in this process, but the underlying mechanisms remain elusive. Here we use the mammalian olfactory system to investigate such mechanisms. Primary olfactory sensory neurons (OSNs) project their axons directly to the olfactory bulb (OB) glomeruli where their synaptic release is subject to local and cortical influence and neuromodulation. Pairing optogenetic ac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In contrast, spontaneous activities, not odor exposure per se, are required for the convergence of axons (Yu et al, 2004). Past studies have shown that pairing an odor with an aversive unconditioned stimulus can lead to enlarged glomeruli corresponding to the cognate receptor, enhanced transmitter release at the OSN termini, and heightened sensitivity to odor stimulation in the interneuron population (Bhattarai et al, 2020;Dias and Ressler, 2014;Jones et al, 2008;Kass and McGann, 2017). Early exposure of odorants can also lead to increased expression of odorant receptor genes and enlarged olfactory glomeruli (Cadiou et al, 2014;Ibarra-Soria et al, 2017;Todrank et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, spontaneous activities, not odor exposure per se, are required for the convergence of axons (Yu et al, 2004). Past studies have shown that pairing an odor with an aversive unconditioned stimulus can lead to enlarged glomeruli corresponding to the cognate receptor, enhanced transmitter release at the OSN termini, and heightened sensitivity to odor stimulation in the interneuron population (Bhattarai et al, 2020;Dias and Ressler, 2014;Jones et al, 2008;Kass and McGann, 2017). Early exposure of odorants can also lead to increased expression of odorant receptor genes and enlarged olfactory glomeruli (Cadiou et al, 2014;Ibarra-Soria et al, 2017;Todrank et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse, a couple of recent works reported brain state-dependent modulation of retinal ganglion cell output in the superior colliculus (Liang et al, 2020; Schröder et al, 2020). Similarly, associative learning influences OSN synaptic release in the mouse olfactory bulb (Bhattarai et al, 2020). Candidate mechanisms proposed include top-down or local circuit-mediated presynaptic modulation at the axonal terminals (Bhattarai et al, 2020), or retinopedal projections-mediated top-down influence directly at the retina (Liang et al, 2020; Schröder et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, associative learning influences OSN synaptic release in the mouse olfactory bulb (Bhattarai et al, 2020). Candidate mechanisms proposed include top-down or local circuit-mediated presynaptic modulation at the axonal terminals (Bhattarai et al, 2020), or retinopedal projections-mediated top-down influence directly at the retina (Liang et al, 2020; Schröder et al, 2020). These hypotheses have the necessary anatomical substrates to support in the mouse.…”
Section: Discussionmentioning
confidence: 99%